PUSAT SUMBER BELAJAR - Purbatua Manurung (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2018)
According to the paradigm of association for education communication technology (AECT) the learning recources are: person, massege, couse material, toola, technique and enviromen. The learning resouces center concist by organize of director of leadher anf staff laboran and admin to manage all activities. In this research as wellas to explained how to construction the learninf resources center aspecially for campus university or school. Kata kunci: sumber belajar, pusat Bahasa